Positive Association between Triglyceride-Rich Lipoprotein Cholesterol and Diabetes Mellitus in Hypertensive Patients. (1st December 2021) - Zhou, Wei; Yu, Yu; Zhu, Lingjuan; Fang, Wangsheng; Tao, Yu; Li, Minghui; Huang, Xiao; Wang, Tao; Bao, Huihui; Cheng, Xiaoshu
Abstract : Background . The association between triglyceride-rich lipoprotein cholesterol (TRL-C) and diabetes mellitus (DM) remains unclear because of limited research and data. The aim of this study was to explore the independent association between TRL-C and DM in hypertensive patients and to examine whether a healthy lifestyle would have an impact on this relationship. Methods . In this study, data from 13, 721 hypertensive patients who were not treated with lipid-lowering drugs were analyzed. TRL-C was calculated from total cholesterol (TC) minus [LDL cholesterol + HDL cholesterol]. DM was defined as fasting plasma glucose of ≥7.0 mmol/L and/or self-reported history of hypoglycemic drug use. Results . After adjusting for potential confounding factors, the TRL-C was significantly positively associated with elevated DM (odds ratio (OR): 1.73 and 95% confidence interval (CI): 1.54–1.94). In subgroup analysis, a healthy lifestyle (HL) failed to modify the positive association between TRL-C and DM (HL: OR 1.93, 95%CI 1.58–2.36; non-HL: OR 1.72, 95%CI 1.50–1.98; P for interaction = 0.38). Conclusion . The results showed a positive association between TRL-C and DM in hypertensive patients. A healthy lifestyle failed to diminish the relationship between TRL-C and DM. The novel findings indicate that TRL-C might be a reliable marker of DM and may provide a new strategy for the prevention and treatment of DM.